Design, analysis and fabrication of loose oil palm fruit picker / Ahmad Amin Zakwan Abu Mawan and Norjasween Abdul Malik - Zakwan, Ahmad Amin; Abdul Malik, Norjasween (School of Mechanical Engineering, 2023)
The oil palm industry has been a significant contributor to Malaysia's national economy and commodity exports. However, a major issue in this industry is the considerable amount of loose oil palm fruit left to rot on the ground. The objectives of this project are to design, analyze, and fabricate a manual machine capable of collecting all the loose oil palm fruit from the ground. This machine aims to save time for users by eliminating the need for manual hand-picking. It operates on a mechanical mechanism, utilizing a chain and conveyor system. Users simply need to push a handle to start the machine. The wheel and bearing mechanism are designed to be suitable for use on uneven surfaces, particularly in oil palm plantations. In conclusion, the product has been successfully designed, analyzed, and fabricated. Extensive product testing has been conducted, demonstrating its ability to collect up to 9kg of loose oil palm fruit per session. This product is expected to offer numerous benefits, particularly to oil palm plantation operators, by streamlining their work and maximizing the utilization of valuable loose oil palm fruit.